Water Quality Assessment of Some Selected Hatcheries at Shambhuganj Mymensingh (Journal of Environmental Science and Natural Resources, 2019)
The study was conducted to investigate the physico-chemical parameters and heavy metals content of water in some selected hatcheries at Shambhuganj, Mymensingh. The water samples were collected from seven selected hatcheries during March to April 2019 to examine temperature, EC, TDS, DO, BOD, pH, ammonia, NO3 -, PO4 2- and heavy metals (Cr, Cd, Pb and Ni). The values of temperature, pH, DO, BOD, EC, TDS and ammonia were 28.5 °C, 7.9 to 8.4, 6.8 to 7.8 mg L-1, 0.1 to 0.9 mg L-1, 231.5 to 307.2 μS cm-1, 146 to 200 mg L-1 and 0.04 to o.06 mg L-1, respectively in the studied hatcheries. The NO3 - and PO4 2- content ranged from 0.48 to 0.68 mg L-1 and 0.45 to 0.63 mg L-1, respectively. Among the heavy metals, Pb was found in 5 hatcheries but the values were within the permissible limit. Other heavy metals (Cr, Cd and Ni) were not found in the studied hatcheries. The fish production of the selected hatcheries ranged from 4 to 9 metric ton. The study results revealed that all of the investigated parameters were within the permissible limit and water quality of selected hatcheries was suitable for fish culture.J. Environ. Sci. & Natural Resources, 11(1-2): 235-240 2018